Slow steaming: economic and legal impacts - Ευγενιτάκη, Μαρία-Ελευθερία (2021)
The charter is a necessary act in the shipping industry in order to transfer cargo from one destination to another around the world. The charter is validated by a charter party. In the second chapter, there is also a division regarding the terms of the charter parties according to English Law. In the third part of this paper, there is analysis of the case of off-hire, which refers to the time charter. The vessel will be off-hire in the event of delay unless caused by breach of contract on the part of the charterer. The fourth part of this thesis analyses slow steaming, the phenomenon of a common practice these years due to the increased bunker prices and the global economic crisis. Slow steaming is the practice of cutting the vessel’s speed in order to save fuels. One of the main purposes of this paper is to provide an analysis of the impacts of slow steaming on economic, environmental, technical and legal fields. Regarding the legal impacts of slow steaming, there are BIMCO clauses for both time charter and voyage charter.